Compressive Strength of Structural Lightweight Concrete Using Styrofoam as an Aggregate Substitution - Abiansyah, Lutfi; Rifdah, Abiyyah (NAROTAMA UNIVERSITY, Indonesia, 2020)
Concrete is one of the important components making up the construction structure. In its development, innovations in the manufacture of concrete both in mixed materials and concrete working methods continue to develop. Lightweight concrete with a mixture of Styrofoam as an aggregate substitution is one of the innovations made as an alternative to natural aggregate which cannot be renewed and can be used up at any time. This study aims to determine the effect of the addition of styrofoam as an aggregate substitution on workability, density, absorption and compressive strength of concrete. The method used in this study is an experimental method of structural lightweight concrete using styrofoam as a substitution of coarse and fine aggregates. Data obtained from testing directly in the laboratory. The variations in the use of Styrofoam as a gross aggregate substitution of 0%, 50%, 100% then continued with 25% and 50% fine aggregate substitution, for the results of density, absorption and compressive strength, respectively decreased as the volume of aggregate substitution increased.